2010
DOI: 10.1016/j.worlddev.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations? The Subjective Well-being of Rural–Urban Migrants in China

Abstract: This paper may be the first to link the literatures on migration and on subjective well-being in developing countries. It poses the question: why do rural-urban migrant households settled in urban China have an average happiness score lower than that of rural households? Three basic hypotheses are examined: migrants had false expectations about their future urban conditions, or about their future urban aspirations, or about their future selves. Estimated happiness functions and decomposition analyses, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
261
2
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(303 citation statements)
references
References 17 publications
30
261
2
10
Order By: Relevance
“…The magnitude of this correlation is similar across specifications and is usually statistically significant, with the exception of the specification related to household members in the remittance-receiving group. Such positive correlation is consistent with the results for developed countries (e.g., Dolan et al, 2008) and also with previous evidence from China (Knight et al, 2009;Knight and Gunatilaka, 2010;Akay et al, 2012). …”
Section: Determinants Of Subjective Well-being In Rural Chinasupporting
confidence: 92%
See 1 more Smart Citation
“…The magnitude of this correlation is similar across specifications and is usually statistically significant, with the exception of the specification related to household members in the remittance-receiving group. Such positive correlation is consistent with the results for developed countries (e.g., Dolan et al, 2008) and also with previous evidence from China (Knight et al, 2009;Knight and Gunatilaka, 2010;Akay et al, 2012). …”
Section: Determinants Of Subjective Well-being In Rural Chinasupporting
confidence: 92%
“…This method allows for identifying positional concerns both for income and consumption of specific goods, such as cars and holidays (see, e.g., Alpizar et al, 2005;Carlsson et al, 2007;Hemenway, 1998, 2005;Akay et al, , 2013. 3 sometimes positive impact from relative concerns (see for South Africa: Kingdon and Knight, 2007;Bookwalter and Dalenberg, 2009;Ethiopia: Akay and Martinsson, 2011;China: Appleton and Song, 2008;Knight et al, 2009;Knight and Gunatilaka, 2010;Akay et al, 2012;Poland: Senik 2004Russia: Ravillion and Lokshin, 2000). 2 One possible explanation of the positive effect is the presence of altruistic feelings towards other members with which the individual interacts in, e.g., the local community.…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to include this group in the present study. However, some studies have investigated SWB among inner-immigrants in China (Akay et al 2012;Jiang et al 2012;Knight and Gunatilaka 2010b;Nielsen et al 2009). These studies have found that SWB among the innerimmigrants was not only worse than that among other urban residents but also worse than that among rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…Easterlin et al 2012). Studies have examined various aspects of the wellbeing of the urban populace (Appleton and Song 2008;Cheng et al 2014c;Frey and Song 1997;Gao et al 2014;Smyth et al 2010;Wu and Tam 2015); rural populace Knight et al 2009;Liang et al 2014b) and rural-urban migrants (Gao and Smyth 2011;Knight and Gunatilaka 2010;Nielsen et al 2010).…”
Section: Introduction and Overviewmentioning
confidence: 99%